Analisis Akuntabilitas Pemerintah Desa Dalam Pengelolaan Alokasi Dana Desa Leyangan Kecamatan Penawangan Kabupaten Grobogan - Nurul Hikmah; Shinta Eka Kartika (Akuntabel: Jurnal Ilmiah Akuntansi, 2024)
This research was conducted in Leyangan Village, Penawangan District, Grobogan Regency. The purpose of this research is to implement village fund allocation along with government transparency in providing accountability information on managing village fund allocations in Leyangan Village, Penawangan District, Grobogan Regency. This study seeks to analyze the accountability of village fund allocation management in Leyangan Village in 2022, namely by comparing the suitability of ADD management practices with applicable regulations. The purpose of this study is to describe the extent of ADD management in Leyangan Village and how the Leyangan village government provides information in realizing village fund allocations. This research was conducted in Leyangan Village, Penawangan District, Grobogan Regency. Data collection was carried out through field observations and interviews. The data analysis technique used in this research is descriptive qualitative analysis. Test the credibility of the data used in this study is to use a triangulation procedure. The results of this study indicate that the management of ADD in Leyangan Village is in accordance with applicable regulations.